Branding and governmentality for infrastructure megaprojects: The role of social media. Issue 1 (January 2019) - Ninan, Johan; Clegg, Stewart; Mahalingam, Ashwin
Abstract: This paper explores subtle strategies that megaproject teams develop in practice to manage stakeholders external to the project team. A governmentality approach is used to account for these strategies. A metro rail megaproject in India provides the case for the study. The strategies were identified through a content analysis of 640 project and non-project based Tweets posted by the metro rail organization. We augmented this dataset with the community's response through social media, as well as through semi-structured interviews that captured the project teams' responses. The findings indicate that the megaproject used various strategies: promoting the organization, giving progress updates, appealing to the community, as well as targeting of specific sections of the population. The effect of these attempts at governmentality through branding were observed in community discourses on social media platforms that echoed the strategic discourses projected by the megaproject while interviews enabled us to access the project team's responses. For the project community, the effects included a positive brand image, creating community brand advocates and building support for the project during contentious episodes. For the project team, the effects included job attraction, enhanced job perception as well as the creation of project team brand advocates. The relation between the governmentality instruments and their corresponding effects are theorized in six propositions. Highlights: The governmentality instruments through branding in social media used by a megaproject are studied. Governmentality effects of practice, knowledge and transformation are identified in project community and project team. The relation between governmentality instruments and governmentality effects are theorized with six propositions.